Informalisation in Low‐wage Labour Markets: a Case Study of the UK Food Industry. Issue 7 (11th April 2017) - Scott, Sam
Abstract: Informalisation is a process that involves the lowering of the floor for pay and working conditions, sometimes legally and sometimes illegally, and it may occur in both formal and informal labour market settings. This paper examines what informalisation looks like in practice in the UK context. Drawing on the experiences of 62 low‐wage migrant workers, employed in the UK food industry, the paper identifies five facets of 'informalisation', namely, job insecurity, work intensification, worker expendability, worker subordination, and employment intermediation. The identification of these five facets of informalisation is important in its own right. In addition, the UK case study also serves to emphasise the fact that the degradation of work is not something that is simply confined to the margins but is evident in the mainstream (beyond irregular workers and beyond the informal economy). Copyright © 2017 John Wiley & Sons, Ltd.